Exploring Muslim Consumers’ Acceptance of Cultured Beef Meat - Rika Terano; Yuji Matsuyoshi; Azrina Azmi Aida; Nurul Nadia Ramli; Zainal Abidin Mohamed (Universitas Muhammadiyah Yogyakarta, 2023)
The advancement in cultured meat research in cellular agriculture has greatly surged. The concerns of halalness and thayibban (cleanliness and permissibility to consume) of cultured beef meat will arise among Muslim consumers, prompting the question, “Who will consume the cultured meat, and are Muslims ready to consume it?” This study aimed to clarify how Muslims perceive cultured meat and the issues surrounding their acceptance. A chi-square test and a binary logistic regression analysis were applied to reveal the acceptance of cultured meat. The results revealed that 44.1% of the respondents accepted cultured meat as their food, while 55.9% expressed doubts due to religious concerns. Their attitudes toward cultured meat influenced their decision to accept it as food. Some consumers had high expectations for cultured meat because they believed it would be superior in taste and have nutritional value and health effects. In conclusion, those Muslims who did not doubt cultured meat accepted it as future food with expectations for better function and value.